Literatur Review: Peran konseling gizi dan senam ergonomik dalam menurunkan kadar asam urat pada penderita gout - Nila Susanti; Yosi Sri Astuti; Harlyanti Muthma'innah Mashar (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2022)
Gout is a disorder caused by inflammation of the joints due to the deposition of uric acid crystals stored in the joints. The causative factors are age, excessive purine intake, obesity, alcoholic beverages, and lack of physical activity. Various efforts can be made to overcome this, including nutritional counseling and physical activity, such as gymnastics. The study aims to provide descriptive information regarding the effect of nutritional counseling on a low-purine diet and ergonomic gymnastics in reducing uric acid levels in patients with gout. Literature review research was conducted using the keywords